2021
DOI: 10.1038/s41386-020-00940-0
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and bipolar disorder are associated with opposite brain reward anticipation-associated response

Abstract: Blunted and exaggerated neuronal response to rewards are hypothesized to be core features of schizophrenia spectrum disorders (SZ) and bipolar disorder (BD), respectively. Nonetheless, direct tests of this hypothesis, in which response between SZ and BD is compared in the same study, are lacking. Here we examined the functional correlates of reward processing during the Incentivized Control Engagement Task (ICE-T) using 3T fMRI. Reward-associated activation was examined in 49 healthy controls (HCs), 52 recento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 65 publications
2
16
1
Order By: Relevance
“…Accordingly, although purely speculative, differences in dopaminergic function in schizophrenia and bipolar disorder in the absence of nicotine (i.e., in non-smokers) may account for the opposing effects of smoking on sensory gating and PRT performance in the two groups. Consistent with this idea, evidence of distinct profiles of reward-anticipation-related neural activation in schizophrenia and bipolar disorder suggest that these disorders may indeed be characterized by differences in dopamine function [ 56 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, although purely speculative, differences in dopaminergic function in schizophrenia and bipolar disorder in the absence of nicotine (i.e., in non-smokers) may account for the opposing effects of smoking on sensory gating and PRT performance in the two groups. Consistent with this idea, evidence of distinct profiles of reward-anticipation-related neural activation in schizophrenia and bipolar disorder suggest that these disorders may indeed be characterized by differences in dopamine function [ 56 ].…”
Section: Discussionmentioning
confidence: 97%
“…A second aim was to compare associations in individuals with schizophrenia to individuals with psychotic bipolar disorder. This is an important comparison because although individuals with bipolar disorder share genetic susceptibility with schizophrenia [ 51 ], experience perceptual disturbances and P50 sensory gating deficits [ 24 , 52 ], and show high rates of smoking [ 53 ], several theoretical models (for reviews, see [ 4 , 54 , 55 ]) and recent empirical studies [ 56 ] suggest a distinct profile of motivational disturbances in bipolar disorder that are potentially attributable to elevated (as opposed to blunted) reward responsiveness. Accordingly, individuals with bipolar disorder may differ from individuals with schizophrenia on important aspects of reward-based prediction and prediction error signaling.…”
Section: Introductionmentioning
confidence: 99%
“…First, the lVS to lvAI/lPut pathway is part of the salience network ( Seeley et al, 2007 ), which is structurally and functionally impaired in schizophrenia ( Palaniyappan & Liddle, 2012 ) and is involved in reward anticipation ( Diekhof et al, 2012 ). Additionally, the AI has been shown to deactivate in patients with schizophrenia during reward anticipation in comparison to healthy controls ( Smucny et al, 2021 ). Accordingly, our results showed a negative correlation between lVS to lvAI/lPut functional connectivity and apathy scores on the BNSS.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of hypoactivity has been confirmed in meta-analyses ( Leroy et al, 2020 , Radua et al, 2015 ), but some studies do not show group differences ( Kirschner et al, 2016 , Stepien et al, 2018 ). Other regions activated during reward anticipation include the anterior cingulate cortex and the insula ( Diekhof et al, 2012 ), which typically show lower activation in patients with schizophrenia ( Cadena et al, 2018 , Leroy et al, 2020 , Moran et al, 2019 , Smucny et al, 2021 ). It should be noted that deficits in reward anticipation are present in other disorders, such as bipolar disorder, although a recent study showed that they may rely on different patterns of activation than in schizophrenia ( Smucny et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While in schizophrenia findings converge towards reduced striatal activation during the processing of reward, this result is less clear in BD. Thus, depending on the task, task stage (anticipation of reward or reward outcome) and patients' clinical state (depressed, euthymic, manic) increased [6][7][8], decreased [4,[9][10][11][12] and similar [3,13,14] brain responses as compared to control participants have been observed in BD.…”
Section: Introductionmentioning
confidence: 99%